Global existence and decay rates of solutions to the viscous water-waves system. (November 2022) - Bae, Hantaek; Lee, Woojae; Shin, Jaeyong
Abstract: In this paper, we analyze a nonlinear model of the viscous water-waves equation proposed in Dias et al. (2008). To this end, we first study the linear model in Dias et al. (2008). We then derive a new model which approximates the nonlinear model in Dias et al. (2008). We finally show the existence of a unique global-in-time solution and its decay rates to this new system with small initial data in energy spaces.